Different Pasts for Different Political Folk: Political Orientation Predicts Collective Nostalgia Content - Stefaniak, Anna; Wohl, Michael Jeremy Adam; Sedikides, Constantine; Smeekes, Anouk; Wildschut, Tim (Frontiers in Political Science, 2021)
Collective nostalgia is a bittersweet emotion that reflects sentimental longing for positively valued aspects of the past of one’s group. Because conservatism is typically associated with a general desire to preserve the societal status quo or return society to its traditional way of being, nostalgia has been theorized to be characteristic of those on the political right (i.e., conservatives). In the current work, we tested the idea that collective nostalgia is experienced by both conservatives and liberals, however, the content of their nostaligizing differs. Across three studies in three unique socio-political contexts—U.S. (Study 1, MTurk, N = 352), Canada (Study 2, student sample, N = 154), and the U.K. (Study 3, online panel, N = 2,345)—we found that both conservatives and liberals experienced collective nostalgia for a more homogenous and more open society of the past. However, conservatives experienced more homogeneity-focused collective nostalgia and liberals experienced more openness-focused collective nostalgia. Replicating previous findings, openness-focused nostalgia emerged as a negative and homogeneity-focused nostalgia as a positive predictor of intergroup prejudice. These results have both theoretical and practical significance for understanding political attitudes and behaviors. To the point, variance in the conservative and liberal political agendas is likely, in part, a function of a difference in their respective predisposition to nostalgize about and thus desire to bring about the return of a particular aspect of the in-group’s past.